2018
DOI: 10.1016/j.vhri.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in a Community Physical Activity Program and Its Effects Upon the Health-Related Quality of Life of Elderly People: A Cross-Sectional Study

Abstract: Background: Aging is related to an increase in the prevalence of noncommunicable diseases and impairments in health-related quality of life. Physical activity is a nonpharmacological intervention that is known to prevent and manage noncommunicable diseases and improve quality of life. Objectives: To compare the quality of life, as measured by the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), of elderly participants and nonparticipants in a community physical activity program. Methods: One hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…En cambio, estas herramientas han mostrado sensibilidad y especicidad entre controles modelos clínicos (Baez et al, 2014;Preckel et al, 2018;Singer y Klimecki, 2014). El efecto techo, o efecto piso, se ha observado en medidas neurocognitivas aplicadas en población aparentemente sana (Aguirre-Loaiza et al, 2019;Barbosa de Lira et al, 2018;McMorris, Turner, Hale y Sproule, 2016). Cuarto, aunque se usaron instrumentos que superan la complejidad de los inventarios y se ubicaron en paradigmas contextuales, aún son necesarias nuevas herramientas que satisfagan exigencias en aplicaciones de la psicología del rendimiento.…”
Section: Discussionunclassified
“…En cambio, estas herramientas han mostrado sensibilidad y especicidad entre controles modelos clínicos (Baez et al, 2014;Preckel et al, 2018;Singer y Klimecki, 2014). El efecto techo, o efecto piso, se ha observado en medidas neurocognitivas aplicadas en población aparentemente sana (Aguirre-Loaiza et al, 2019;Barbosa de Lira et al, 2018;McMorris, Turner, Hale y Sproule, 2016). Cuarto, aunque se usaron instrumentos que superan la complejidad de los inventarios y se ubicaron en paradigmas contextuales, aún son necesarias nuevas herramientas que satisfagan exigencias en aplicaciones de la psicología del rendimiento.…”
Section: Discussionunclassified
“…Several other studies have found that participation in an exercise program resulted in better health perceptions. Namely, three studies have shown that, among older adults, participation in a community exercise group, in a Pilates exercise group, or in Tai Chi has resulted in better health perceptions [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Regular and proper physical exercise will help maintain the normal functioning of the brain and nerves [32,33]. In general, a lot of evidence shows that participating in regular physical exercise has great benefits for the physical health of the elderly, and it also benefits and slows down the aging process [34][35][36][37]. Therefore, public space in the neighborhood should attract the elderly to go and carry out sports activities.…”
Section: Elderly Health and Space Environmentmentioning
confidence: 99%